Study and Optimization of Existing Ventilation System of Public Buses Using Computational Fluid Dynamics - Gurung, Lava; Sapkota, Nishan; Shrestha, Krishna Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Among all of the public transport, public buses are the major means of transportation for the people on daily basis. In both urban as well as in rural areas, a large number people travel through public bus regularly. Despite of this usage, public buses in developing countries like Nepal are equipped with minimum or zero facilities to the passengers. The maximum number of public buses, used for medium and short routes, are not air-conditioned and air has to be regulated naturally throughout the bus to provide the passengers with adequate thermal comfort. Furthermore, the operating buses are old, noisy and uncomfortable. With rising pollution in the environment, there is also a high chance of passenger compartment being contaminated with pollutants like particulate matters since there is frequent movement of people in peak hours. Therefore, as a solution to these problems, the research is being carried out. The study and optimization of the existing ventilation system of the buses enabling the efficient flow of air ensuring better thermal comfort for the passenger is accomplished. The bus operation region is accordance to Nepal city area and especially summer temperature is focused. The interior design of the bus is with reference to TATA star bus series and the manlike shape of the passengers are as per Body Mass Index (BMI) of Nepalese people and 3D designed in Solidworks. Through several number of design modifications and test using computational fluid dynamics, finally the design with the optimum result is selected and advised to be opted for efficient performance of ventilation in public buses. For the CFD simulations turbulence model of k-epsilon and tetrahedral mesh is applied in ANSYS. And with a mean observation, among all the roof vents orientations, the case with roof ventilation at the front and backside provides the optimum result among the optimized design with effective temperature of 305.53 K and mean velocity of 14.77 m/s.